2020
DOI: 10.3390/ijms21041180
|View full text |Cite|
|
Sign up to set email alerts
|

Hydrogen Sulfide as Potential Regulatory Gasotransmitter in Arthritic Diseases

Abstract: The social and economic impact of chronic inflammatory diseases, such as arthritis, explains the growing interest of the research in this field. The antioxidant and anti-inflammatory properties of the endogenous gasotransmitter hydrogen sulfide (H 2 S) were recently demonstrated in the context of different inflammatory diseases. In particular, H 2 S is able to suppress the production of pro-inflammatory mediations by lymphocytes and innate immunity cells. Considering these biological effects of H 2 S, a potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 168 publications
(200 reference statements)
1
21
0
Order By: Relevance
“…Since H 2 S is a common byproduct of cysteine degradation (42, 43), the ability of butyrate producers to synthesize L-cysteine could be related to the potential for elevated H 2 S production in the low gout cluster. These predictions along with previous studies showing H 2 S as a possible inducer of inflammation (44, 45) suggested a possible role for H 2 S specifically and sulfur-containing amino acids more generally in the perturbed microbiota of gout patients. As observed with amino acids, maximal production of the seven non-differentially produced byproducts was similar between the two clusters with elevated synthesis by Bacteroides in the high gout cluster being balanced with increased synthesis by butyrate producers and Megamonas in the low gout cluster (Fig.…”
Section: Resultssupporting
confidence: 78%
“…Since H 2 S is a common byproduct of cysteine degradation (42, 43), the ability of butyrate producers to synthesize L-cysteine could be related to the potential for elevated H 2 S production in the low gout cluster. These predictions along with previous studies showing H 2 S as a possible inducer of inflammation (44, 45) suggested a possible role for H 2 S specifically and sulfur-containing amino acids more generally in the perturbed microbiota of gout patients. As observed with amino acids, maximal production of the seven non-differentially produced byproducts was similar between the two clusters with elevated synthesis by Bacteroides in the high gout cluster being balanced with increased synthesis by butyrate producers and Megamonas in the low gout cluster (Fig.…”
Section: Resultssupporting
confidence: 78%
“…The studies mentioned above and numerous others have employed inhibitors of CSE and CBS (PAG and AOAA, respectively), L-cysteine and the H 2 S donors NaHS and GYY4137, as well as Cse −/− mice within various macrophage inflammatory models, which clearly established H 2 S as an effector molecule involved in resolution of inflammation by driving macrophages toward an anti-inflammatory M2 phenotype ( Castelblanco et al., 2018 ; Zhou et al., 2019 ; Sunzini et al., 2020 ). Similarly, macrophages infected with Mtb exhibited increased CSE expression and H 2 S levels leading to an anti-inflammatory or M2 macrophage phenotype.…”
Section: The Physiological Importance Of H 2 Smentioning
confidence: 99%
“…The role of H 2 S in vascular diseases, inflammation, critical illness, reperfusion injury, various nervous system diseases, metabolic diseases and cancer was extensively reviewed [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Evidence in support of a role of H 2 S deficiency in vascular disorders, such as hypertension and atherosclerosis, is accumulating [ 79 , 80 ].…”
Section: H 2 S As a Gasotransmittermentioning
confidence: 99%